2023
DOI: 10.3233/bmr-220301
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic trunk training on pain, disability, and strength in non-specific low back pain patients: A systematic review and meta-analysis

Abstract: BACKGROUND: Low back pain is one of the leading causes of disability globally, with a high economic and social burden. A decrease or imbalance in trunk strength has been associated with the occurrence of low back pain and its severity. Trunk strength training is helpful in the treatment of Non-specific low back pain (NSLBP) patients. However, we do not know the effects of trunk isokinetic training (IKT) on pain intensity, disability, and trunk strength. OBJECTIVE: This systematic review aimed to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Maintaining physical activity and avoiding bed rest can reduce pain and restore function in both acute and chronic LBP [8][9][10]. Even though previous research has sought to identify the best forms of physical activity to treat chronic LBP, the results have been inconclusive [11][12][13][14][15][16]. While higher levels of physical activity have been previously associated with less disability [17], this correlation has been sometimes only loose [3,18], and it has been suggested that pain and disability can even worsen due to physical activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining physical activity and avoiding bed rest can reduce pain and restore function in both acute and chronic LBP [8][9][10]. Even though previous research has sought to identify the best forms of physical activity to treat chronic LBP, the results have been inconclusive [11][12][13][14][15][16]. While higher levels of physical activity have been previously associated with less disability [17], this correlation has been sometimes only loose [3,18], and it has been suggested that pain and disability can even worsen due to physical activity [19].…”
Section: Introductionmentioning
confidence: 99%